Women, Islam and resistance in the Arab world - Holt, Maria; Jawad, H. A. (Boulder, Colorado : Lynne Rienner Publishers, Inc., 2013)
How are women in the Arab world negotiating the male-dominated character of Islamist movements? Is their participation in the Islamic political project including violent resistance against foreign invasion and occupation the result of coercion, or of choice? Questioning assumptions about female powerlessness in Muslim societies, Maria Holt and Haifaa Jawad explore the resistance struggles taking place in Lebanon, Iraq, Palestine, and elsewhere in the Middle East from the perspectives of the women involved. The authors make extensive use of vivid personal testimonies as they examine the influence of such factors as religion, patriarchy, and traditional practices in determining women s modes of participation in conflicts. In the process, they add to our knowledge not only of how women are affected by political violence, but also of how their involvement is beginning to change the rules that govern their societies.
Includes bibliographical references and index.
Keywords: Women -- Arab countries -- Social conditions; Women and religion -- Arab countries; Women and war -- Arab countries; Political participation -- Arab countries -- 21st century; Arab Spring, 2010-